Connectivity and biological valuation: tools to assess the ecological coherence of networks of marine protected areas - Gomes, Inês Alves dos Santos Teixeira (2019)
In order to avoid, reduce and offset the impact that human activities are having on the health of the world's oceans, the international demand for a successful ecosystem-based approach to the marine environment is growing in popularity. Major European maritime policies and other international agencies advocate that, in order to effectively protect the marine environment, there is a need to establish ecologically coherent networks of marine protected areas (MPAs). Achieving ecological coherence is, however, a complex task given the magnitude of the concept and the lack of clear operational definitions. Therefore, assessing ecological coherence requires multiple approaches to analyse not only the location, size and spacing of protected sites already selected for protection, but also infer about new sites to enhance network effects. The aim of this thesis is to develop and use different tools to assist, support and help to promote the assessment of the ecological coherence of networks of MPAs, with a focus on continental Portugal. Three complementary methods were applied using the mussel Mytilus galloprovincialis as a model species to estimate connectivity via larval dispersal along the Portuguese west coast. The first study described the use of natural geochemical tags to trace back natal origins of mussels and describe direct measures of demographic connectivity patterns (dispersal trajectories and distances). It focused in the Arrábida and Berlengas Marine Protected Areas (MPAs) and emphasized the significance of source and sink populations and self-recruitment within MPAs. The second study resulted from the need to quantify mussel bed coverage in order to apply the connectivity estimates into broader scale models of larval dispersal. The use of low altitude and high-resolution drone imagery, 3D surface models and ground-based observations proved to be a viable and powerful tool for surveying intertidal ecosystems at an ecological relevant spatial scale. The effect of environmental variables (substrate complexity and wave exposure) on mussel density and size was also investigated. Maximum mussel density occurred at intermediate values of wave exposure in winter while smaller sized mussels prevailed at high values of wave exposure. The combination of the empirical connectivity estimates, with mussel demographic and biological parameters (reproductive output, larval behaviour, mortality) allowed the validation of a broad scale numerical biophysical model in the third study This model combined oceanographic and demographic information with larval biology, and was used to simulate dispersal of M. galloprovincialis larvae along the Western Iberian coast. The biophysical model simulated and accounted for uncertainty of the geochemical method in the assignment of source populations and resulted in unprecedented levels of correspondence among independent connectivity estimates at small spatial scales. This fine-tuned model can be used in the future to investigate metapopulation dynamics with applications in MPA management strategies. Finally, a quantitative-based ecological approach was used to value biodiversity along the Portuguese continental shelf. The marine biological valuation protocol summarized and combined existing biological and ecological spatial information of different ecosystem components into an overall map of marine biological value, highlighting hotspots of ecological significance. This study also evaluated the extent to which high biological value was contained in the current and projected Natura 2000 sites in Portugal. By integrating the information of marine connectivity pathways, with a broad biological assessment of the Portuguese coast, this thesis seeks to build upon existing MPA assessment criterion and take a step forward in making it practical and applicable to the Portuguese setting.